2023
DOI: 10.1155/2023/3727265
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infection and Associated Factors among Pregnant Women Receiving Antenatal Care at a Primary Health Care Facility in the Northern Region of Ghana

Ezekiel K. Vicar,
Samuel E. K. Acquah,
Williams Wallana
et al.

Abstract: Urinary tract infection (UTI) is frequently encountered during pregnancy and is associated with adverse maternal, fetal, and neonatal effects. However, very little information is available on the prevalence of UTI among pregnant women in the northern part of Ghana, a region with a high birth rate. This study employed a cross-sectional analysis of the prevalence, antimicrobial profile, and risk factors associated with UTI in 560 pregnant women attending primary care for antenatal check-ups. Sociodemographic obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
4
2
1
1
Order By: Relevance
“…The finding in this study is in line with the findings by Kulkarni et al (2014) who reported 21.47% prevalence, and indicates that Escherichia coli was the commonest isolate (47.36%), followed by Klebsiella pneumoniae (19.2%), Pseudomonas aeruginosa (14.10%), Staphylococcus aureus (3.5%) and Enterococcus faecalis (5.2%). It also corroborates the findings of Orji et al (2022) and Vicar et al (2023). Table 2 shows the prevalence of bacterial isolates associated with CAUTIs in relation to gender.…”
Section: Resultssupporting
confidence: 86%
“…The finding in this study is in line with the findings by Kulkarni et al (2014) who reported 21.47% prevalence, and indicates that Escherichia coli was the commonest isolate (47.36%), followed by Klebsiella pneumoniae (19.2%), Pseudomonas aeruginosa (14.10%), Staphylococcus aureus (3.5%) and Enterococcus faecalis (5.2%). It also corroborates the findings of Orji et al (2022) and Vicar et al (2023). Table 2 shows the prevalence of bacterial isolates associated with CAUTIs in relation to gender.…”
Section: Resultssupporting
confidence: 86%
“…An ampicillin, tetracycline, chloramphenicol, and cotrimoxazole combination was also found to have multidrug resistance, with ceftriaxone (6.3%), ciprofloxacin (11%) and amikacin (9.9%) having lower resistance percentages (Newman et al, 2011). This observation suggests that the current prevalence of AMR per the WHO ACCESS classification agrees with previous studies (Jia et al, 2023;Vicar et al, 2023).…”
Section: Multidrug Resistance Isolates As Defined By Ecdc-mdrsupporting
confidence: 91%
“…E. coli, the most frequently isolated organism was resistant to both Ceftriaxone and Cefuroxime at 94.1% and to Cloxacillin at 100%. This has been demonstrated in other studies where resistance values obtained in this study were higher than those mentioned in the studies (Johnson et al, 2021;Ghaima et al, 2018;Caneiras et al, 2019;Vicar et al, 2023). The irrational use and abuse of broad-spectrum antibiotics due to their affordability and easy access may be the reason for the high resistance to these drugs (Afoakwa et al, 2018;Newman et al, 2011).…”
Section: Discussionsupporting
confidence: 75%